Concurrent validity of the Warner Initial Developmental Evaluation of Adaptive and Functional Skills and the Bayley Scales of Infant and Toddler Development, Third Edition. (18th November 2020) - Peyton, Colleen; Msall, Michael E; Wroblewski, Kristen; Rogers, Elizabeth E; Kohn, Michael; Glass, Hannah C
Abstract : Aim: To determine the concurrent validity of the Warner Initial Developmental Evaluation of Adaptive and Functional Skills (WIDEA‐FS), a criterion‐specified questionnaire that assesses a child's adaptive skills in everyday contexts, and the Bayley Infant and Toddler Scales of Development, Third Edition (Bayley‐III). Method: In a prospective cohort study, 431 WIDEA‐FS and Bayley‐III assessments were completed among 341 children, aged 10 to 36 months corrected age (158 females, 183 males; median [interquartile range] gestational age at birth 32wks [29–38]), monitored in a high‐risk neonatal intensive care unit follow‐up clinic. Results: WIDEA‐FS scores were significantly associated with Bayley‐III scores in all domains. Lower scores on the WIDEA‐FS were significantly associated with an increased risk of adverse developmental performance on all Bayley‐III scales. The association was strongest for motor and language Bayley‐III scores when tested at <30 months of age, and for cognitive Bayley‐III scores when tested at ≥30 months of age. Interpretation: The WIDEA‐FS has concurrent validity with the Bayley‐III and may be a useful tool in high‐risk follow‐up settings. What this paper adds: WIDEA‐FS mobility, communication, and social cognition domains are concurrently valid in infants at high‐risk for neurodevelopmental disability. Bayley‐III motor, language, and cognitive composite scores are concurrently valid in the same group. The WIDEA‐FS mobility and communication domains may be most clinically useful in children <30 months. What this paper adds: WIDEA‐FS mobility, communication, and social cognition domains are concurrently valid in infants at high‐risk for neurodevelopmental disability. Bayley‐III motor, language, and cognitive composite scores are concurrently valid in the same group. The WIDEA‐FS mobility and communication domains may be most clinically useful in children <30 months.